An Introduction to Health Psychology - Gatchel R. J.; Baum A.; Krantz D. S.; Singer J. E. (New York St. Louis San Francisco Auckland McGraw-Hill Publishing Company, 1989)
This text offers a multidisciplinary approach, covering the social, clinical and biological concerns around issues in health psychology. It presents a balanced treatment of the basic research, including applied issues, theory, assessment, treatment and biopsychological and clinical approaches. This edition includes: expanded coverage of the changing health environment; the growing importance of prevention; and updated coverage of cancer research and psycho-neuroimmunology.
Keywords: 159.9